Flexible Learning Strategies in Yoruba Education - Fagunwa, Diipo (West African Journal of Open and Flexible Learning, 2016)
This paper is a reflection on Yoruba indigenous education (hereafter called Yoruba education) and its flexible learning strategies. It describes flexible learning as a learning practice that empowers the student with control over, what he learns and how he learns it. The paper highlights that Yoruba education is a complex education system. It is holistic, fundamental and integrated with an all-encompassing curriculum. Yoruba education is sophisticated, organised, well managed and cohesive with a vast subject that comes as integrated knowledge. The Yoruba individual was inducted with Yoruba education into mores, customs, principles, and payees of the Yoruba society. The paper identifies the tools used in Yoruba education and how these are applied in a flexible way to get the best outcomes.
Keywords: Yoruba; Indigenous education; mores; customs; principles